ASSESSING THE SATISFACTION LEVEL OF NURSING STUDENTS TOWARDS CLINICAL PLACEMENT ACROSS ACADEMIC YEAR IN PRIVATE NURSING COLLEGES AT CHARSADDA (The Research of Medical Science Review, 2025)
Aim: The aim of this research was to assess the satisfaction of undergraduate nursing students regarding their clinical placements in Private Nursing Colleges at Charsadda. Method: A cross-sectional survey was conducted with nursing students from private nursing colleges in Charsadda. An adapted questionnaire was used from a study published in 2023 to assess their clinical satisfaction in different areas, such as mentorship, availability of resources, and interactions with instructors. The sample consisted of 70.2% male and 29.8% female students belonging to both third and fourth-year academic levels. Results: Many students experienced the clinical placements with low to moderate satisfaction. Only 20.8% demonstrated high satisfaction, while 42.3% reported a low satisfaction level. Fourth-year students were satisfied more than third-year students, and there was a positive correlation between academic progression and clinical comfort. General hospital setting: Allocation to general hospitals provided exposure to a wide range of clinical experiences but had several stressors regarding the level of acuity and availability of resources (77.4%). Conclusion: Much lies behind the influencing factors for clinical satisfaction regarding nursing students it is growing with a greater emphasis on the improvement of mentorship, resource allocation, and gender-sensitive support. The development of such areas would improve the experiences of learning and potential satisfaction levels of the students. Future longitudinal approaches within a diversified setting of research will dissect causative factors relating to clinical satisfaction.